Examining the role of luxury brands in ytopia - Marchegiani, Chris; Latter, Chelsey (School of Marketing, Curtin Business School, 2009)
A vast body of knowledge exists with regards to the attitudes involved in the consumption of luxury brands. The purchase of products for their symbolic and social value rather than for their inherent utility in now widely recognised as a significant determinant of consumer behaviour (Mason 1992). With changes in industry trends, gaps in knowledge are created. Thus, it is important to examine luxury brands in relation to uniqueness. Moreover, whether consumers need for uniqueness is in fact a need for status in this younger emerging market. This research plans to integrate earlier research from two academic areas that have examined uniqueness. First there is considerable research in psychology on how consumers use possessions to define identity (Knight and Kim 2007; Belk 1988; Campbell 1995; Clark, Zboja, and Goldsmith 2007; Goldsmith and Clark 2008; O'Cass and Frost 2002; Phau and Leng 2008; Simonson and Nowls 2000; Tian, Bearden, and Hunter 2001). Second marketing has examined how a variety of factors influence the consumption of certain products and brands. Studies have found for example, that status seeking consumers are concerned with their peers and use brands to convey this message (O'Cass and Frost 2002; Ruvio, Shoham, and Brencic 2008). This paper will give a detailed description and analysis of the previous literature relating to the key constructs in this field. To begin with, a background of the constructs in the literature will be discussed. Followed by a discussion of how the constructs have been employed in previous studies. In the course of the review process, various gaps in the literature will be acknowledged for further study.